The Role of BAZNAS Cirebon City in the Collection and Distribution of Zakat at IAIN Cirebon in Religious Social Welfare - Nurherawati, Irma Nurherawati; Akmal, Mikdadul Akmal Dul; Putri, Zahra Aulia; Fadlan, Muhamad Fadlan; Saumantri, Theguh (Rumah Moderasi Beragama of Cyber Islamic University Syekh Nurjati Cirebon, 2024)
This research aims to analyze the role of the Cirebon City National Zakat Amil Agency (BAZNAS) in the process of collecting and distributing zakat funds at the Cirebon State Islamic Institute (IAIN) and its impact on socio-religious welfare. BAZNAS as the official institution that manages zakat has an important responsibility in ensuring that zakat funds are collected optimally and distributed on target. This research uses a qualitative approach with descriptive methods, involving in-depth interviews with related parties at BAZNAS and IAIN Cirebon, as well as analysis of relevant documents. The research results show that BAZNAS Cirebon City has succeeded in increasing the collection of zakat funds through various education and outreach programs, as well as improving the distribution system to be more targeted. The positive impact of the distribution of zakat funds can be seen in increasing socio-religious welfare within the IAIN Cirebon environment, including increasing access to education for underprivileged students and strengthening religious activities. This research provides recommendations for developing more effective zakat collection and distribution strategies to achieve broader social and religious welfare.